Explosive Oil Prices - Marc Gronwald (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper deals with three aspects of spectacular oil price episodes such as the one witnessed in 2008. First, the concept of temporary explosiveness is proposed as an empirical method for capturing this type of behavior. The application of a recently proposed recursive unit root test shows that phases of explosive behavior occurred in 1990/1991, 2005/2006, and 2007/2008. Second, the underlying causes of the observed behavior are discussed. The prevailing opinion in the literature is that fundamental factors are the main explanation for the 2007/2008 oil price hike, but that in 1990/1991, speculative demand shocks also played a role. Third, it is shown that temporary oil price hikes influence economic decisions that are based on oil price information. For this purpose, a real options model on the oil field development decision is reconsidered. The mechanism behind this is an increase in the profitability of the oil field development project. In sum, the key contributions of this paper are to highlight a new empirical feature in oil prices and to show that economic effects of speculative demand shocks can emerge that to date appear to have been overlooked.
Keywords: C12; C58; D81; Q30; 330; oil prices; explosiveness; uncertainty; real options; climate change; speculative demand shocks